Enhancing Security and Operational Efficiency in Tourisms Sectors through Blockchain Technology: The Role of Trust and Regulatory Environment under institutional economics - Kumar. S , Santhosh; Sateeshchandra, Navya Gubbi; Chelabi , Kaddour; Hadziahmetovic, Nereida; Sambiri, Benjamin Bensam; Ray, Samrat (Journal of Ecohumanism, 2025)
Purpose: The tourism industry is more and more turning to cutting-edge technologies to tackle issues concerning security, operational effectiveness, and confidence. The decentralized, transparent, and unchangeable characteristics of blockchain technology provide a revolutionary opportunity to improve these areas. This study investigates how blockchain can protect operational processes, secure data, and support service providers and regulators. This research explores the relationship between trust, technology adoption, and regulation by suggesting ways to incorporate blockchain in the tourism industry with a focus on both innovation and responsibility. Design/methodology/approach: The study used quantitative methods to survey 326 professionals in the tourism industry and frequent travelers to explore their interactions with tourism services based on blockchain technology. Data underwent analysis through the utilization of SPSS and SmartPLS 4. This method sought to comprehend the various viewpoints on the advantages and difficulties of incorporating BCT into their activities. Findings: This study Outcomes show the blockchain adoption is perceived. Although some believe that BCT has the potential to improve security and operational efficiency, there are also positive opinions on the matter. Both customers and providers agree on BCT's trustworthiness, however, they have differing opinions on privacy and security improvements. Moreover, the research highlights the crucial importance of regulatory enforcement in promoting blockchain adoption, as blockchain presents valuable chances for ensuring compliance and reducing risks. Implication: This study adds to the current knowledge by offering perspectives from service providers and customers on blockchain technology in the travel sector. It highlights the challenges of integrating new blockchain technologies and urges further research to tackle the raised issues, providing a fresh perspective on utilizing distributed ledger technologies to improve security and operational effectiveness